Pollach, Edith (audio interview #2 of 4) - Pollach, Edith (3/2/1921 - 11/30/2007); Pfister, Janet, interviewer
INTERVIEW DESCRIPTION - This is the second of four interviews with Edith Pollach. The interview consists of one tape. It was conducted by a friend of Pollach's. The audio quality of the interview is good. 2/9/1999